2021
DOI: 10.3390/agronomy11040714
|View full text |Cite
|
Sign up to set email alerts
|

The Most Important Fungal Diseases of Cereals—Problems and Possible Solutions

Abstract: The level of cereal yields and the quality of these yields depend, to a large extent, on a crop management system, the genetic potential of a given cultivar, but also on factors that may cause damage to plants or a reduction in yield. Such factors include fungal diseases of cereals, which may cause a reduction in yield by 15–20%, and in extreme cases even by 60%. The main factors determining the occurrence of these pathogens are the weather conditions during the growing season of plants, crop rotation, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…On the other hand, the production of aflatoxins brings the more severe consequence of A. flavus presence in the maize fields, but what also should be taken into account are economic losses due to maize fungal infection. Fungal diseases of cereals can cause a yield reduction in the range from 15-20%, but even more in some extreme cases (60%) [51].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the production of aflatoxins brings the more severe consequence of A. flavus presence in the maize fields, but what also should be taken into account are economic losses due to maize fungal infection. Fungal diseases of cereals can cause a yield reduction in the range from 15-20%, but even more in some extreme cases (60%) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Multi-year studies of tw-type mutants have revealed the significant variation in MGG expression observed in the seed material from different years and statistically significant differences in MGG levels between the allelic tw-type mutants (Table 1). Naturally, among the most important factors that influence the occurrence of fungal diseases is weather conditions during the growing season [27][28][29]. However, another source of such variations may lie in the highly variable expressivity of the tw phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…During autumn when temperatures drop, the pathogen produces ascospores, which are released in the summer when it is warm. Ascospores can survive winter on plant residues and may be a source of infection in the spring [ 7 ]. The B. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%